2011
DOI: 10.1371/journal.pone.0025252
|View full text |Cite
|
Sign up to set email alerts
|

An Important Role for Syndecan-1 in Herpes Simplex Virus Type-1 Induced Cell-to-Cell Fusion and Virus Spread

Abstract: Herpes simplex virus type-1 (HSV-1) is a common human pathogen that relies heavily on cell-to-cell spread for establishing a lifelong latent infection. Molecular aspects of HSV-1 entry into host cells have been well studied; however, the molecular details of the spread of the virus from cell-to-cell remain poorly understood. In the past, the role of heparan sulfate proteoglycans (HSPG) during HSV-1 infection has focused solely on the role of HS chains as an attachment receptor for the virus, while the core pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 56 publications
(72 reference statements)
1
13
0
1
Order By: Relevance
“…Our results are also in the same range (i.e. less than a log difference) observed by others in recent studies analyzing the impact of cellular proteins on HSV or HIV proliferation [55], [56], [57], [58], [59], [60], [61]. Multi-log inhibitions where therefore not expected in the present study but it does naturally make it more difficult to ascribe a functional role to present host proteins.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are also in the same range (i.e. less than a log difference) observed by others in recent studies analyzing the impact of cellular proteins on HSV or HIV proliferation [55], [56], [57], [58], [59], [60], [61]. Multi-log inhibitions where therefore not expected in the present study but it does naturally make it more difficult to ascribe a functional role to present host proteins.…”
Section: Discussionsupporting
confidence: 90%
“…Syndecan-1 has been implicated in HSV-1 entry into various cell types. 18 As shown in Figure 6, the uninfected cornea showed that syndecan-1 is expressed abundantly in the corneal epithelium, with some accentuation in the basal cells. There was also some staining of cells in the stroma.…”
Section: Effect Of Hsv-1 Infection On the Expression Of A Heparan Sulmentioning
confidence: 84%
“…After 4 h, cells were washed 3 times with 1ϫ PBS and once with citrate buffer (pH 3) to remove any bound virus particles. The Western blot assay was performed according to protocols described previously (21). Briefly, whole-cell lysates were denatured in NuPAGE LDS sample buffer (NP0007; Invitrogen, Carlsbad, CA) and heated to 86°C for 8 min before gel loading.…”
Section: Methodsmentioning
confidence: 99%